The influence of preoperative hormonal stimulation on hypospadias repair - Nathan Colin Wong; Nathan Colin Wong; Luis H Braga; Luis H Braga (Frontiers Media S.A., 2015)
Androgen stimulation to temporarily promote penile growth has been commonly used to facilitate hypospadias repair. Although some series suggest improvement in both functional and cosmetic outcomes, a recent systematic review and meta-analysis showed a possible relationship between preoperative hormonal stimulation and higher complications. As a result, indications and treatment regimens remain controversial. Here, we review the available literature and present our clinical practice.